South Africa : Financial Sector Assessment Program-Technical Note on Insurance Sector - Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2022)
The South African insurance sector is large, complex, internationally active, and competitive. Supported by high penetration and density of insurance products, the insurance sector has grown to account for 18 percent of the financial sector in South Africa. The industry hosts an unusually diverse range of business models, including traditional participation focused models, bank-led conglomerates, asset management focused groups, and technology driven new entrants. Even among large insurers, risk profiles vary significantly, which is unique relative to other major insurance markets. Most large insurance groups are actively expanding their business both regionally and globally.